Comparison of the Temporary Diagnostic Relief of Transforaminal Epidural Steroid Injection Approaches: Conventional versus Posterolateral Technique - Lee, I.S.; Kim, S.H.; Lee, J.W.; Hong, S.H.; Choi, J.-Y.; Kang, H.S.; Song, J.W.; Kwon, A.K. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Conventional transforaminal epidural steroid injection (TFESI) has several problems. The purpose of this study was to compare the temporary diagnostic relief and advantages of TFESI performed using the conventional and posterolateral approaches.METHODS: From August to December 2004, 187 patients received TFESI for lumbar radicular pain. A total of 108 patients (65 women, 43 men; mean age, 56 years) fulfilled the inclusion criteria. In essence, the needle target point was the “safe triangle,” but if there was a possibility that the needle could penetrate the nerve root or that the injectate could contact spinal nerve, posterolateral TFESI was used as an alternative. Image analyses of needle positions and chart reviews were performed. Logistic regression analysis and t test were used for statistical analysis.RESULTS: Of the 108 patients, 75 (69.4%) showed an improvement at 2 weeks after TFESI. In 46 patients (42.6%), the needle was located in the posterolateral epidural space, and 33 (71.7%) of those experienced pain relief. Of the 62 patients in whom the needle was located in the anterior epidural position, 42 (68%) experienced pain relief. There was a significant reduction in pain sense for the posterolateral approach (P < .05). However, no statistical difference was found between the 2 approaches and temporary diagnostic relief, and no correlation was found between the other variables tested and temporary diagnostic relief (P > .05).CONCLUSION: Our findings suggest that the posterolateral approach is an alternative method for TFESI in cases where needle tip positioning in the anterior epidural space is difficult.